Análise da viabilidade técnica e econômica da irrigação em híbridos de milho - Ben, Luis Humberto Bahú (2018)
Due to the water deficit irrigation is important for the stability of the maize crop productivity. However, due to the costs involved, the analysis of the economic viability of irrigation is fundamental to justify its investment. Especially in corn hybrids due to their adaptation to different growing environments. Thus, this work aimed to analyse the production and economic viability of supplemental irrigation in different maize hybrids. The experiment was conducted in the city of Santiago/RS, in the crops of 2015/2016 (crop I) and 2016/2017 (crop II) in a randomized complete block design with five irrigation depths (0, 50, 75, 100 and 125% of ETc), four maize hybrids in the I crop and six hybrids in the II crop. The number of ears per plant, number of grains per ear, mass of 100 grains, grain yield and water use efficiency were evaluated. Through the hybrids production function and the costs related to and not related to fixed sprinkler irrigation for 1 ha area, the net revenue (RL) was obtained in the maximum efficiency irrigation depths (Wm), optimal (Wo) and equivalent (We) and in the treatment without irrigation, and the net present value (NPV), the internal rate of return (IRR) and the cost benefit (B/C) ratio. In addition, fixed sprinkler irrigation projects were developed for areas of 1, 3, 5, 10, 15, 20 and 25 ha and slopes of the 7 and 15% settling pipes, and the costs and the occurrence of economies of scale. There was a better distribution of rainfall in crop II than in crop I, so irrigation depths influenced, in the two harvests, the mass of 100 grains, productivity and water use efficiency, and the number of grains per spike in the I crop. different production functions and Wm among hybrids. In relation to RL, crop I was higher for all irrigated hybrids, with different values among hybrids. In the second crop, only one of the hybrids presented higher RL, in relation to the non-irrigated. The NPV, IRR and B / C were variable among the hybrids, the crops and the blades. In relation to the costs for the different areas, there was an increase, with the increase of the size of the area. Therefore, irrigation increases the productive performance of the hybrids, between 9.9 and 41% and the technical irrigation management can be performed between the depths of 90.6 and 105.4% of the ETc. Hybrids AG 9025, P 1630 and DKB 290 presented better agronomic performance, with yields between 16,281.3 and 13,609.1 kg ha-1. The RL, NPV, IRR and R / C indicate that irrigation utilization is economically viable for most hybrids. The economic management of irrigation can be performed using irrigation depths between 74.3 and 90.1% of the ETc to obtain the highest RL, being dependent on the hybrid. AG 9025 provided the highest RL of the hybrids (between R$ 2,805.51 and R$ 1,804.64 ha-1), and the increase in the size of the irrigated area provides diseconomies of scale.